2008
DOI: 10.1111/j.1551-2916.2008.02406.x
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Induced Relaxor Behavior in PbSc0.50Nb0.25Ta0.25O3 Thin Films: A Comparison with Nanoceramics

Abstract: Comparative studies of the microstructure, micro‐Raman spectroscopy, and dielectric properties of PbSc0.50Nb0.25Ta0.25O3 (PSNT) thin films and nanoceramics were carried out over a wide range of temperature (100–520 K) and frequency (100 Hz to 1 MHz). The microstructure of PSNT films revealed an in‐plane compressive strain, whereas PSNT nanoceramics showed an average grain size of 10–15 nm although these nanoordered regions are not capable of producing relaxor behavior. We have observed a shift of 65 K in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…With the increase of mismatch effect between the films and substrates, the grain size became smaller. 20,21 In the work of Ziebert et al 22 on ͑Pb, Ca͒TiO 3 ͑PCT͒ and Pb͑Sc, Nb͒O 3 ͑PSN͒ films, it was also found that the FE relaxor behavior was grain size dependent. 18,19 In order to give a better illustration of the broadening of the diffuse phase transformation, the curves of the reduced dielectric constant ͑ / max ͒ at 1000 kHz as a function of the reduced temperature ͓ = ͑T − T m ͒ / T m ͔ are given in Fig.…”
Section: Phase Transformation Charactersmentioning
confidence: 97%
“…With the increase of mismatch effect between the films and substrates, the grain size became smaller. 20,21 In the work of Ziebert et al 22 on ͑Pb, Ca͒TiO 3 ͑PCT͒ and Pb͑Sc, Nb͒O 3 ͑PSN͒ films, it was also found that the FE relaxor behavior was grain size dependent. 18,19 In order to give a better illustration of the broadening of the diffuse phase transformation, the curves of the reduced dielectric constant ͑ / max ͒ at 1000 kHz as a function of the reduced temperature ͓ = ͑T − T m ͒ / T m ͔ are given in Fig.…”
Section: Phase Transformation Charactersmentioning
confidence: 97%
“…Typical ferroelectric relaxor character can be observed around the dielectric permittivity peak, in contrast, the same character cannot be detected in Pb (1− x ) Ba x ZrO 3 bulk ceramics with Ba 2+ substitution at x < 0.3 . This difference can be attributed to the mismatch effect between the film and substrate and the smaller grain size . Although the dielectric permittivity (ε m ~ 1650 at 100 Hz) is higher compared with those found in PZT‐based compositions, it is rather lower than that obtained in corresponding sintered bulk PBZ ceramics with the same composition (ε m ~ 12000), which may most probably be due to the limited film thickness.…”
Section: Resultsmentioning
confidence: 74%
“…22 The contribution of dipole fluctuations in PNRs to the dipole polarization increases with increasing the volume fraction of PNRs, while the relaxation frequency of dipole polarization decreases with increasing the volume fraction of PNRs. 18,[23][24][25] The increase in dipole and the decrease in the relaxation frequency observed in Figs. 3 and 6 could be interpreted as increase of the volume fraction of PNRs with decreasing temperature.…”
Section: Resultsmentioning
confidence: 80%